Kritisk oversigt over engelske og danske juridiske ordbøger - Nielsen, Sandro (HERMES - Journal of Language and Communication in Business, 1989)
Ideally, special-purpose dictionaries should have complex macro- and micro-structures compiled according to strictly defined lexicographic principles. A surprisingly large number of the English and Danish law dictionaries examined leave much to be desired from a lexicographic point of view, and in some cases improvements and changes are proposed. Different types of definition, the presentation of lemma signs and equivalents, and meaning discrimination as well as their value to the user are discussed. It is suggested that the optimal special-purpose dictionary for learners should include both encyclopaedic and linguistic information whether it be a monolingual or bilingual dictionary.